Biografi novel Zain Hashim - Buang Haji Umar, 1962-; Buang Haji Umar, 1962-; Dewan Bahasa dan Pustaka (Kuala Lumpur : Dewan Bahasa dan Pustaka, 1997)
Autobiography of Zain bin Hashim, Sarawak nationalist.
Keywords: Zain Hashim, -- 1920-1991; Nationalists -- Sarawak -- Biography; Sarawak -- Biography